Predictors of poor cardiac recovery pattern after aortic declamping in consecutive cardiac surgery cases - Karmacharya, RM; Xigang, G; Jianjie, G; Haichen, W; Yang, Y; Yongxin, L (Nepalese Heart Journal, 2013)
Background Poor Cardiac recovery following aortic declamping in cardiac surgery is associated with increased morbidity and mortality. This study aims to identify the predictors of poor cardiac recovery pattern after aortic declamping in consecutive cardiac surgery cases. Methods A prospective study was conducted from February 2011 to November 2011in elective cardiac surgical cases in First Affiliated Hospital of Medical College of Xi’an Jiaotong University. Single factor and subsequent logistic regression analysis was performed to identify the predictors of poor cardiac recovery pattern after aortic declamping. Results Of the 150 patients enrolled in the study, 38% had good cardiac recovery while 62% had poor cardiac recovery after aortic declamping. Of the studied variables, those associated with significant outcome (P value <0.05) in all the subgroups were NYHA (New York Heart Association) classification (1 or 2 vs. 3 or 4), Control group vs. blood cold cardioplegia, Route of cardioplegia, Age, Cardiopulmonary Bypass time groups, aortic clamping duration, ejection fraction and presence of pulmonary hypertension. From multivariate logistic regression analysis for predictors of cardiac recovery pattern, it was found that Age more than 40 years, NYHA category 3 or 4, ejection fraction less than 55%, aortic clamping time 60-120 minutes were significantly associated with poor cardiac recovery pattern. Cardiopulmonary bypass time however was not significantly associated as independent predictors of poor cardiac recovery pattern after aortic declamping. Conclusion Age more than 40 years, NYHA category 3 or 4, ejection fraction less than 55%, aortic clamping time 60-120 minutes are independent predictors of poor cardiac recovery pattern after aortic declamping. DOI: http://dx.doi.org/10.3126/njh.v9i1.8341 Nepalese Heart Journal Vol.9(1) 2012 pp.10-15